LAMPhimerus: A novel LAMP assay for detecting Amphimerus sp. DNA in human stool samples. - William Cevallos; Pedro Fernández-Soto; Manuel Calvopiña; Cristina Fontecha-Cuenca; Hiromu Sugiyama; Megumi Sato; Julio López Abán; Belén Vicente; Antonio Muro (Public Library of Science (PLoS), 2017)
Amphimeriasis is a fish-borne disease caused by the liver fluke Amphimerus spp. that has recently been reported as endemic in the tropical Pacific side of Ecuador with a high prevalence in humans and domestic animals. The diagnosis is based on the stool examination to identify parasite eggs, but it lacks sensitivity. Additionally, the morphology of the eggs may be confounded with other liver and intestinal flukes. No immunological or molecular methods have been developed to date. New diagnostic techniques for specific and sensitive detection of Amphimerus spp. DNA in clinical samples are needed.A LAMP targeting a sequence of the Amphimerus sp. internal transcribed spacer 2 region was designed. Amphimerus sp. DNA was obtained from adult worms recovered from animals and used to optimize the molecular assays. Conventional PCR was performed using outer primers F3-B3 to verify the proper amplification of the Amphimerus sp. DNA target sequence. LAMP was optimized using different reaction mixtures and temperatures, and it was finally set up as LAMPhimerus. The specificity and sensitivity of both PCR and LAMP were evaluated. The detection limit was 1 pg of genomic DNA. Field testing was done using 44 human stool samples collected from localities where fluke is endemic. Twenty-five samples were microscopy positive for Amphimerus sp. eggs detection. In molecular testing, PCR F3-B3 was ineffective when DNA from fecal samples was used. When testing all human stool samples included in our study, the diagnostic parameters for the sensitivity and specificity were calculated for our LAMPhimerus assay, which were 76.67% and 80.77%, respectively.We have developed and evaluated, for the first time, a specific and sensitive LAMP assay for detecting Amphimerus sp. in human stool samples. The procedure has been named LAMPhimerus method and has the potential to be adapted for field diagnosis and disease surveillance in amphimeriasis-endemic areas. Future large-scale studies will assess the applicability of this novel LAMP assay.